Development of Digital Biology Teaching Materials to Revitalize Post Covid-19 Biology Learning - Tias Pratama, Anggi; Triatmanto; Subiantoro, Agung Wijaya; Handziko, Rio Christy; Anazifa, Rizqa Devi (Berpusi Publishing, 2023)
This research carried out the first few stages namely Define, the second stage was Design, the next stage was Develop and the last was Dissemination. From each of these steps, there are several steps that need to be carried out. In the Define step, there are 5 stages that need to be taken. 1) front-end analysis , 2) learner analysis , 3) task analysis , 4) concept analysis , and 5) specifying instructional objectives. These five steps aim to map the needs of students and also the needs of the learning process. The hope is that the product to be developed can truly answer the needs of learning and students appropriately. In the second stage, is Design. There are 4 activities that need to be carried out during the Design stage, namely 1) constructing criterion-referenced tests , 2) media selection , 3) format selection , and 4) initial design. This Design stage is the result of the embodiment of the analysis carried out in the Define stage. Of course, the hope at this design stage is that the resulting product design is a product that is suitable and in accordance with the conditions of the perpetrators of the learning process, especially students as learners. In the Develop stage, the initial product produced from the Design stage is reviewed by experts and professionals, and tested on product users. Input from experts and professionals as well as input from product users, becomes a reference for consideration in revising the product being developed. The goal is that users can actually do learning according to their knowledge. If the product has passed the test at the develop stage and revisions have been carried out, then the next stage is the dissemination of the use of the resulting product. what really needs to be considered at this final stage is the choice of platform or container that will be used as a medium for disseminating the teaching materials that have been prepared.